Comparative study of students' civic engagement in heterogeneous and homogeneous sociocultural environements: Case study of Croatian Students - Roje, M. (Array, 2013)
This collaborative research project aims at investigating the civic engagement of student populations in different socio-cultural environments. The problem of this study was to explore how the grade sociocultural heterogeneity affects the level of civic engagement in Croatian students’ populations. According to Wegner (1991), by increasing the number of people raised in different environments around an individual, the grade of sociocultural heterogeneity of one’s environment increases, as well. We used mixed methodology, combining quantitative research and qualitative research, in form of focus groups. A sample of 537 participants took part in the construction of the questionnaire designed to measure 3 factors of civic engagement (civic indicators, electoral indicators and indicators of political voice). Furthermore, we tested the differences among 2 groups of participants (N=100 in each group) classified as follows: Croatians studying in UK, and Croatians studying in Croatia. The latter group was further subdivided into three: (1) those studying in their hometown ; (2) those that have moved to study in a different Croatian town, and (2) those that had moved to study in Zagreb (capital). Our aim was to measure and compare civic engagement in each of four groups in order to verify the hypothesis described above. The result are discussed according to Keeter’s 2002) concept of civic engagement and Diu’s (2005) hypothesis of diaspora, combined with theories of social learning. This research has valuable implications for understanding the importance of a multicultural educational experience for the development of civic engagement. Furthermore, it directly supports the EWU policies on international education mobility programs and highlights long-term benefits of Croatian membership for the growth of civic engagement.